2008
DOI: 10.1016/j.addr.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of dichloroacetate in the treatment of genetic mitochondrial diseases

Abstract: Dichloroacetate (DCA) is an investigational drug for the treatment of genetic mitochondrial diseases. Its primary site of action is the pyruvate dehydrogenase (PDH) complex, which it stimulates by altering its phosphorylation state and stability. DCA is metabolized by and inhibits the bifunctional zeta-1 family isoform of glutathione transferase/maleylacetoacetate isomerase. Polymorphic variants of this enzyme differ in their kinetic properties toward DCA, thereby influencing its biotransformation and toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 41 publications
(65 reference statements)
5
124
0
Order By: Relevance
“…Ongoing studies on the cell line specific glycolytic phenotype along with the cell line specific expression of the different PDK isoforms, Kv1.5 channels, and antiapoptotic proteins will further clarify these issues. Tolerable DCA dosages of 25 mg/kg/d given twice daily, which were clinically applied for the treatment of mitochondrial disorders, resulted in peak plasma concentrations of 100-250 µmol/L after the first dose and 200-550 µmol/L after 6 month of therapy [23]. Plasma concentrations of about 1 mmol/L were observed after the first application of 50 mg/kg DCA as well as after chronic exposure to 25 mg/kg DCA [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies on the cell line specific glycolytic phenotype along with the cell line specific expression of the different PDK isoforms, Kv1.5 channels, and antiapoptotic proteins will further clarify these issues. Tolerable DCA dosages of 25 mg/kg/d given twice daily, which were clinically applied for the treatment of mitochondrial disorders, resulted in peak plasma concentrations of 100-250 µmol/L after the first dose and 200-550 µmol/L after 6 month of therapy [23]. Plasma concentrations of about 1 mmol/L were observed after the first application of 50 mg/kg DCA as well as after chronic exposure to 25 mg/kg DCA [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting PDK, DCA activates PDH, which increases the provision of acetyl CoA to the Krebs cycle and, in turn, stimulates oxidative phosphorylation. By shifting the metabolism of glucose from glycolysis and lactate formation to mitochondrial oxidative phosphorylation, DCA reduces lactate concentrations and reverses the Warburg effect in pulmonary artery smooth muscle cells and cancer cells (Archer et al, 2008;Stacpoole et al, 2008;Michelakis et al, 2010). For these reasons, the mitochondrion is considered to be the primary cellular site of DCA action.…”
Section: Introductionmentioning
confidence: 99%
“…DCA has been reported as a possible pharmacological cure for chronic diseases such as lactic acidosis and other mitochondria associated diseases (Michelakis et al 2010;Miquel et al 2012;Stacpoole et al 2008). In a number of in vitro studies, DCA is reported to enhance reactive oxygen generation (ROS) generation and oxidative stress leading to cell death (Ayyanathan et al 2012;Hassoun and Ray 2003;Wong et al 2008).…”
mentioning
confidence: 99%